2014
DOI: 10.1111/dth.12136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TNF-α serum level in patients with recalcitrant multiple common warts, treated by lipid garlic extract

Abstract: No universal consensus about optimal modality for treating the recalcitrant multiple common warts (RMCW). The objective of the study was to evaluate the immunological mechanisms and clinical therapeutic effect of using lipid garlic extract (LGE) in the treatment of RMCW. The study included 50 patients with RMCW. They were randomly assigned into two groups: the first group (25 patients) received LGE, and the second group (25 patients) received saline as a control group. In both groups, treatments were made to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
(34 reference statements)
0
11
0
1
Order By: Relevance
“…Garlic has long been used in traditional and complementary medicine [ 119 ] and several clinical trials have demonstrated the efficacy of its administration or application in resolving symptoms associated with warts [ 120 ], denture stomatitis [ 121 ], venous ulcers [ 122 ], and skin wounds [ 85 , 123 ]. For example, in preclinical studies AGE showed wound healing potential in a dose-dependent manner after six days application [ 123 , 124 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
See 1 more Smart Citation
“…Garlic has long been used in traditional and complementary medicine [ 119 ] and several clinical trials have demonstrated the efficacy of its administration or application in resolving symptoms associated with warts [ 120 ], denture stomatitis [ 121 ], venous ulcers [ 122 ], and skin wounds [ 85 , 123 ]. For example, in preclinical studies AGE showed wound healing potential in a dose-dependent manner after six days application [ 123 , 124 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…Treatment of wart virus by improving immune system might be accomplished by intralesional immunotherapy [ 125 , 126 ] and it may damage all sores on the body [ 127 ]. A randomized control study showed that lipid portion of GE two times daily for four weeks had greater potential on patients with recalcitrant multiple common warts compared to any other treatment, through the modulation of TNF-α serum level as well as the promotion of immunotherapy [ 120 ]. Similarly, denture stomatitis expresses a common form of chronic oral candidiasis and a randomized clinical trial study demonstrated that GE at 40 mg/mL three times per day could be a potential substitution for denture stomatitis treatment compared with nystatin [ 121 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…2nd stage efficacy study with three parallel groups (42 treated children, 41 placebo control and 73 benzimidazole) RCTs with two parallel groups; 120 subjects including 60 in each group with mean age 26 yrs Aged garlic extract AGE capsule (2.56 gm/cap) One capsule/day for 90 days Placebo, AGE capsule (n = 60) and placebo (n = 60) Reduction of severity of cold and flu illness, days of symptom exists, number of incidences and work/school missed as well the role of specific innate-like lymphocytes (γδ-T cell and NK cell) and antioxidant parameters ( Nantz et al, 2012 ; Percival, 2016 ) a. garlic extract group and One placebo capsule/day for 90 days b. placebo group (M = 48 and F = 72) RCTs with two parallel groups; Lipid garlic extract group (M = 6 and F = 19) and 50 subjects including 25 in each group with mean age 25 + yr Lipid garlic extract LGE applied to the largest one of recalcitrant Placebo (saline), placebo applied twice day for 28 days LGE (n = 25) and placebo (n = 25) Size of warts and photographic comparison. The response was considered complete (complete disappearance), partial (reduced size in 25%–100%) and no response (0–25% decrease in size) as well as also examined serum TNF-α (0 and 4th week) and adverse effect up to 6 months placebo group (M = 20 and F = 5) multiple common warts (RMCW) twice per day for 28 days Kenawy et al (2014) RCTs with four parallel groups of 88 subjects; 79 subjects including appx. 20 in each group of chronic hepatitis with different age DDB with garlic oil Capsule contains 25 mg DDB plus 50 mg garlic oil (group B 2 cap/day; group C 3 cap/day; group D 6 cap/day; for 42 days with 7 days follow-up) Placebo, Capsule (n = 22/21/17) and placebo (n = 19) Changes in surrogate marker ALT and AST for hepatitis liver injury by HBV or HCV.…”
Section: Introductionmentioning
confidence: 99%
“…Allyl methyl disulfide from fresh garlic can treat the immunological disorders, such as ulcerative colitis, Crohn's disease, and intestinal inflammation [ 53 ]. Lipid garlic extract as an immunotherapy has better cure rates for the recalcitrant multiple common warts [ 133 ]. Fresh aqueous garlic and onion extracts play an important role in enhancing immune function [ 102 ].…”
Section: Chronic Disease Prevention Of Allium Gmentioning
confidence: 99%